2020
DOI: 10.1103/physrevb.101.064302
|View full text |Cite
|
Sign up to set email alerts
|

Many-body dynamical localization in the kicked Bose-Hubbard chain

Abstract: We show that a clean kicked Bose-Hubbard model exhibits a dynamically many-body localized phase. This phase is characterized by ergodicity breaking persisting in the thermodynamic limit: the system does not heat up to infinite temperature, whatever the initial state, and the Floquet states violate eigenstate thermalization. Differently from many-body localization here the entanglement entropy linearly increases in time. This increase corresponds to space-delocalized Floquet states which are nevertheless locali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…When J = 0, the Hamiltonian (1) behaves as the operatorV , therefore it shows massively degenerate eigenspaces, as elucidated in Ref. [17]. If we switch on a small value of J U , we find a strong mixing inside the eigenspaces, while different eigenspaces interact starting from second perturbative order in J/U .…”
Section: Appendix A: Derivation Of the Effective Xxz Model Via Perturmentioning
confidence: 52%
See 1 more Smart Citation
“…When J = 0, the Hamiltonian (1) behaves as the operatorV , therefore it shows massively degenerate eigenspaces, as elucidated in Ref. [17]. If we switch on a small value of J U , we find a strong mixing inside the eigenspaces, while different eigenspaces interact starting from second perturbative order in J/U .…”
Section: Appendix A: Derivation Of the Effective Xxz Model Via Perturmentioning
confidence: 52%
“…A striking example is dynamical localization (initially discovered for one degree of freedom [14] and later generalized to the many body case [15][16][17][18]), where a classical ergodic driven system shows a regular-like behavior in the quantum regime, leading to a suppression of energy absorption. Another example is many body localization.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a single kicked rotor, quantum coherence strongly suppresses heating through dynamical localization in energy space [32,33]. Accordingly, it was recently shown that dynamical localization can lead to ergodicity breaking in many-body kicked models, such as coupled rotors [34] and the Bose-Hubbard model [35]. However, as conjectured in Ref.…”
Section: Discussionmentioning
confidence: 92%
“…This phenomenon has a dynamical counterpart originally studied in the context of the kicked rotor [3][4][5][6]. Localization is an extremely broad subject that extends to the hydrogen atom in a monochromatic field [7,8], Rydberg atoms [9], quantum billiards [10][11][12][13][14][15][16], banded random matrices [17], interacting systems [18][19][20][21][22], and kicked interacting systems [23][24][25][26], among others.…”
Section: Introductionmentioning
confidence: 99%